Design and Build a KIT Humoris (Ohm's Law for Dynamic Electricity) for Science Learning in Junior High School - Rizky Agassy Sihombing; Siti Darmilah; Umi Sayidatus Zakiya; Muslim Muslim; Ida Kaniawati; Sjaeful Anwar (Universitas Lambung Mangkurat, 2024)
The role of tools as educational media is crucial in facilitating the learning of scientific concepts, allowing students to master science materials and develop their skills effectively. This research aims to develop a KIT as an experimental approach to learning focused on investigating the relationships among voltage, current, resistance, and power. This study employs a research and development (R&D) approach to design and implement an impactful science learning tool for science experiments. The envisioned impact of this learning tool is to captivate students' interest and concept understanding in science education, especially in Ohm's law for the dynamic electricity topic. The design of the KIT Humoris is specifically structured to establish and illustrate the relationships between voltage, current, and resistance, as well as to calculate power based on voltage and current values. The user-friendly design and visually appealing features of the KIT Humoris make it a practical tool that enhances the tangible understanding of science concepts. Integrating this tool with the Merdeka Curriculum allows teachers to customize lessons according to the unique needs of their students. The design process involves meticulous planning, prototype development, and continuous evaluation to ensure the tool's effectiveness. Results from the trial phase indicate heightened student engagement, improved conceptual understanding, and a profound practical learning experience. KIT Humoris is a valuable science learning tool, providing an engaging and practical approach aligned with the Merdeka Curriculum. Its successful implementation increases student enthusiasm and a deeper comprehension of scientific principles. The implications are contributing to the innovation of teaching methods, especially in the context of the Merdeka Curriculum. From a practical standpoint, the tool has a positive impact on students and their understanding of science concepts.